First Outbreak of Aeromoniasis, Caused by Aeromonas veronii, in Farmed European Seabass (Dicentrarchus labrax) in the Ionian Sea, Greece - Eirini Lampou; Eleni Psychari; Konstantina Louka; Charalampos Kotzamanidis; Andigoni Malousi; Ioannis Petropoulos; Markos N. Kolygas; Dimitrios Doukas; Konstantina Bitchava (Pathogens, 2025)
This article documents the first outbreak of aeromoniasis caused by Aeromonas veronii in farmed European seabass (Dicentrarchus labrax) along the Greek Ionian Sea coast. In late spring 2024, commercially sized fish exhibited anorexia, hemorrhages, and ulcers on the skin, accompanied by elevated morbidity and mortality rates. The outbreak spread rapidly across local farms in Sagiada Bay, reaching its peak in late summer, and extending into the Astakos Gulf, southern in the Ionian Sea. The postmortem examination revealed hemorrhages, organomegaly, abscess formation, and granulomatous inflammation. Aeromonas veronii was isolated from all examined individuals in nutrient media and confirmed by biochemical and molecular methods. Whole genome sequencing and phylogenetic analysis demonstrated genetic homogeneity among two strains from two different areas along the Ionian Sea and a close evolutionary relationship with other Aeromonas veronii strains from the Aegean Sea. Although genetically similar, the isolates exhibited differences in phenotypic and biochemical characteristics, indicating regional variability. The present study provides an overview of the pathology, clinical characteristics and progression of aeromoniasis in Ionian Sea aquaculture, highlighting the need for continued monitoring, in-depth genomic and phenotypic assessment, and the design of region-specific preventive strategies, including autogenous vaccines, for effective disease management.